Using a Triple Helix approach to examine interactions and dynamics of innovation in less-favoured regions: The case of the Portuguese Polytechnic of Guarda - Natário, Manuela (2017)
Using the Triple Helix model, this article examines the contribution of a higher education institution, the Polytechnic of Guarda (PG), located in an inland, a less-favoured region of Portugal, to territorial innovation dynamics. The main goal is to explore how the interaction and cooperation between the three helices of the Guarda region (PG, companies and local governance institutions) fosters innovation and development in a less-favoured region in a sustainable way, generating new patterns of collaboration among the helices. The study investigates the behaviour of the three helices through an online survey. The results suggest that PG has a key role in building a knowledge-based society, in advancing innovation and the development of the region. Its role in business dynamics and community development through knowledge transfer and entrepreneurship training is reflected mainly in the high proportion of businesses and institutions of the local governance system that have workers trained in this institution, and in the satisfaction (medium and high) with the work performed by professionals trained at PG. Although the other helices (companies and local governance institutions) are also involved in innovation to different degrees, the innovation performance of the region remains low because of weak interactions between companies and PG, and between companies and local governance institutions. However, a closer relationship is identified between local governance institutions and PG.